Sęp zasępił się strasznie, osowiała sowa… Translation problems in the German version of the poem Figielek by Julian Tuwim (Free your mind: Reflections on language, literature and culture, 2022)
This article discusses the main problems in the translation of Polish poem “Figielek” by Julian Tuwim into German. In the theoretical part, the author focuses on untranslatability and describes various definitions of this phenomenon and translation strategies (transformations), which can be used to deal with untranslatability. The analytical part is devoted to wordplays and sound devices (in form of verbal animal derivatives), which cause difficulties in the translation of the poem “Figielek”. The analysis of the German version should illustrate, which solutions were used by the translator to deal with untranslatability.